2017
DOI: 10.1071/cp17169
|View full text |Cite
|
Sign up to set email alerts
|

Identification of quantitative trait loci underlying seed oil content of soybean including main, epistatic and QTL×environment effects in different regions of Northeast China

Abstract: Oil content is a primary trait in soybean and determines the quality of soy food, feed and oil product. Increasing oil content is a major objective of soybean breeding. The aims of the present study were to identify quantitative trait loci (QTLs) and epistatic QTLs associated with oil content in soybean seed by using 129 recombinant inbred lines derived from a cross between cultivar Dongnong 46 (oil content 22.53%) and the semi-wild line L-100 (oil content 17.33%). Phenotypic data were collected from 10 tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…In present study, PVE of A and AE of 64 additive QTL ranged from 1.29% to 10.75% and 0.86% to 10.66%, respectively, while those of AA and AAE effect of 12 pairs of epistatic QTL ranged from 1.61% to 3.31% (Figure 3 and Table 5). By the comparison, AA and AAE effect were less than A and AE effect, this is similar to the study of Teng et al (2017) [22]. Epistasis may also play an essential role in trait improvement even if epistatic variance components are low [17,54].…”
Section: Genetic Basement Of Epistasis Qtl and Interactions With Envisupporting
confidence: 83%
See 1 more Smart Citation
“…In present study, PVE of A and AE of 64 additive QTL ranged from 1.29% to 10.75% and 0.86% to 10.66%, respectively, while those of AA and AAE effect of 12 pairs of epistatic QTL ranged from 1.61% to 3.31% (Figure 3 and Table 5). By the comparison, AA and AAE effect were less than A and AE effect, this is similar to the study of Teng et al (2017) [22]. Epistasis may also play an essential role in trait improvement even if epistatic variance components are low [17,54].…”
Section: Genetic Basement Of Epistasis Qtl and Interactions With Envisupporting
confidence: 83%
“…Epistasis, interaction between one pair of loci located in the same or different chromosomes, as an important genetic basis of complex traits [18]. Some studies had shown that epistasis signi cantly affected the expression of genes and genetic variation underlying soybean [17,[19][20][21][22][23][24]. Hou et al(2014) [20] mapped oil content QTLs using simple repeat sequence (SSR) markers derived from Charleston and Dongnong594, which detected 4 pairs oil epistatic effect QTLs, and Qi et al (2017) [12] identi ed epistatic interactions for seed oil content under multi-environments based on a high-density single-nucleotide polymorphisms (SNP) using the same population.…”
Section: Introductionmentioning
confidence: 99%
“…In a literature study, approximate moisture analysis of black cumin seed found that crude protein ranged from 20.6 to 31.2%, ash ranged from 3.9 to 4.8%, fats ranged from 22.6 to 53.4%, carbohydrates varied from 24.9 to 34%, and moisture ranged 3.8 to 7.4% [2,4,6,16,17]. The black seed had higher fat content than corn (10%) [18] and soybean (20%) [19], suggesting that the black seed would be a suitable source for oil industry applications. Additionally, the black seed is an excellent source of fats and proteins for humans.…”
Section: Proximate Composition Of Black Seed Powdermentioning
confidence: 99%
“…As shown in Table 1, the moisture, lipid, protein, and ash contents of P. macrocarpa seed were 6.23%, 43.34%, 15.21%, and 3.90%, respectively. The lipid content exceeded that of many common oil crops, such as soybean (∼20%) (Teng et al., 2017) and corn (∼11%) (Navarro et al., 2016), suggesting P. macrocarpa seed may be suitable for the oil industry application.…”
Section: Resultsmentioning
confidence: 93%